2022
DOI: 10.1182/bloodadvances.2021005666
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of patients with von Willebrand disease: summary of 2 systematic reviews of the literature

Abstract: von Willebrand disease (VWD) is the most common inherited bleeding disorder. The management of patients with VWD who are undergoing surgeries is crucial to prevent bleeding complications. We systematically summarized the evidence on the management of patients with VWD who are undergoing major and minor surgeries to support the development of practice guidelines. We searched Medline and EMBASE from inception through October 2019 for randomized clinical trials (RCTs), comparative observational studies, and case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…It indicated that keeping the FVIII and VWF levels above 0.50 IU ml À1 for at least three consecutive days ensured efficient haemostasis (considered as 'excellent' by the researchers after 74 to 100% of major procedures) and a low risk of complications, but there was a high level of uncertainty in this evidence. 255 Consequently, the VWD guidelines recommend that the duration of therapeutic intervention and specific target levels should be individualised based on the patient, type of procedure and bleeding history, as well as availability of VWF and FVIII testing. 254 High-quality studies are also needed for haemophilia patients because there is no consensus on the optimal replacement therapy and the minimum required haemostatic levels for individual factors.…”
Section: Evidence Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…It indicated that keeping the FVIII and VWF levels above 0.50 IU ml À1 for at least three consecutive days ensured efficient haemostasis (considered as 'excellent' by the researchers after 74 to 100% of major procedures) and a low risk of complications, but there was a high level of uncertainty in this evidence. 255 Consequently, the VWD guidelines recommend that the duration of therapeutic intervention and specific target levels should be individualised based on the patient, type of procedure and bleeding history, as well as availability of VWF and FVIII testing. 254 High-quality studies are also needed for haemophilia patients because there is no consensus on the optimal replacement therapy and the minimum required haemostatic levels for individual factors.…”
Section: Evidence Summarymentioning
confidence: 99%
“…275 It should be noted that if DDAVP is used to increase VWF levels, there is the potential for tachyphylaxis after several doses in addition to the potential for more significant hyponatraemia. 255 Use of DDAVP is contraindicated in patients with type 3 VWD because of a lack of efficacy and in type 2B VWD because of increased platelet binding and subsequent thrombocytopenia. 254 As DDAVP boosts plasma levels of both VWF and FVIII, it could be the treatment of choice for patients with mild haemophilia A when FVIII can be raised to appropriate therapeutic levels and the WFH recommends the use of DDAVP for peri-operative haemostasis in these patients if there is a good therapeutic response in presurgical testing.…”
Section: Desmopressinmentioning
confidence: 99%
“…The questions were prioritized by the guideline panel based on areas of significant need in the field of VWD, along with input from an international survey of clinicians, patients, and caregivers. 18 As part of this project, other SRs were developed to cover the perioperative management 40 and VWF prophylaxis in patients with VWD (manuscript submitted). 41 In this SR, we found mostly very-low-certainty evidence from comparative observational studies and case series.…”
Section: Discussionmentioning
confidence: 99%
“…Minor bleeding [41] Major bleeding [41] Plasma-derived products 30-60 units/kg 40-60 units/kg 20-40 units/kg every 8-24 hours may be required Single-dose for minor bleeding and for up to 14 days after significant bleeding or surgery [42] Recombinant von Willebrand factor (rVWF) 40-50 IU/kg [43] 60-80 IU/kg [43] Subsequent doses of rVWF can be given at 40-60 units/kg every 8 to 24 hours An infusion rate of 2-15 units/kg/hour can be used [45]. Continuous infusion is also used in patients with acquired VWD and patients with alloantibodies against infused VWF Continuous infusion of VWF concentrates can reduce the clearance of infused products and decrease the total therapeutic dose and cost by as much as 50% [44] Factor VIII 50 units/kg Should be used with the initial rVWF dose to raise factor VIII by 100 IU/dL [43] VWD: Von Willebrand disease.…”
Section: Vwf Concentratesmentioning
confidence: 99%
“…Continuous infusion of VWF concentrates at a rate of 2-15 units/kg/hour can reduce the clearance of infused products, lower the total therapeutic dose and reduce cost by as much as 50% [44,45]. Continuous infusion is also used in patients with acquired VWD and alloantibodies against infused VWF.…”
Section: Vwf Concentratesmentioning
confidence: 99%